Electrochemical and chemical methods of metallizing plastic films - Chapples, J. (Cranfield University, 1991)
This thesis describes two novel techniques for the metallization of non-electroactive polymer films and thicker sectioned polyethylene and nylon substrates. In the first approach, non-electroactive polymer substrates were impregnated with surface layers of polypyrrole and polyaniline, using electrochemical and chemical methods of polymerization. The relative merits of both these approaches are discussed and compared with other methods in the literature. The resultant composite materials exhibited sufficient conductivity to permit the direct electrodeposition of metal surface coats. Polypyrrole coated substrates were also metallized using chemical methods. Cyclic voltammetry studies and scanning electron microscopy of metal coated polypyrrole, showed that metal deposition occurred mainly at the polymer surface by a mechanism of instantaneous nucleation and growth. Using optimized deposition conditions, both electrochemical and chemical metal deposition methods were used to deposit highly reflecting and coherent metal layers onto conducting polymer coated materials. The second approach of metallizing polymers, was the metallization of non-electroactive polymer films by the electroreduction of silver from non-aqueous based silver plating solutions. The effects of the electrode substrate, the deposition potential, and the concentration of metal ions in solution were investigated to determine suitable metal salt/solvent, and polymer film/solvent combinations. The resultant metallized polymer films were evaluated using optical and scanning electron microscopy, ac impedance, and reflectance measurements. These studies enabled the optimum deposition conditions to be determined, and these were subsequently used for the preparation of high quality, uniform, and reflective metal coated films. The results for the electrodeposition of silver into polymer films using the latter approach are compared with those obtained from alternative electrochemical and chemical methods of metallizing polymer films.